The ABU HAMID'S APPLICATION OF ISLAMIC ECONOMICS AL-GHAZALI ON THE ROLE OF MONEY IN THE CONTEXT OF THE MURSALAH PROBLEM: ABU HAMID'S APPLICATION OF ISLAMIC ECONOMICS AL-GHAZALI ON THE ROLE OF MONEY IN THE CONTEXT OF THE MURSALAH PROBLEM - Dina, Dina Anisya R; Mugiyati, Mugiyati (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
Abstract: Islamic economics, as an integral part of Islamic teachings, has a firm view on the issue of wealth in general, including money in particular. Within this framework, Islamic economics has a unique perspective on money, explaining the types and functions of money, as well as setting parameters that guide Muslims on permissible and impermissible actions in financial matters. The uniqueness of Imam Al Ghazali's views on economic aspects, both in general and specifically related to money, is an interesting thing to explore and investigate. This research is a library research with a descriptive approach. That is by describing or explaining Abu Hamid Al-Ghazali's thoughts about money in the perspective of maslahah mursalah. The relevance of Imam al-Ghazali's thoughts on Islamic economics in the book Ihya' 'Ulum al-Din to contemporary (conventional) economics has been able to provide a good solution. Based on Islamic law by implementing the concept of maslahah mursalah, including in managing finances properly, producing goods and services according to community needs and conducting muamalah activities in accordance with existing ethics. Islamic economics according to Imam al-Ghazali in its achievement must prioritize the benefit of society. Economic goals should not only be concerned with one side of life alone, but must be balanced between the world and the hereafter